MOTH (INSECTA : LEPIDOPTERA) DIVERSITY IN MONTANE GUNUNG PATUHA PROTECTED FOREST, WEST JAVA, INDONESIA - Research Center for Biology-LIPI, Widyas - (Masyarakat Zoologi Indonesia, 2009)
Sutrisno, H. 2009. Moth (Insecta : Lepidoptera) Diversity in montane Gunung Patuhaprotected forest, West Java, Indonesia. Zoo Indonesia 18(2): 69-78. A study onmontane moth diversity was conducted at Gunung Patuha protected fores, West Javat.The aim of the study was to evaluate the biodiversity of this montane protected forestusing moths as an indicator. For comparison, biodiversity data of other submontaneforests (G. Kendeng & G. Botol, Halimun National Park, West Java) and a low landforest (Giam Siak Kecil Nature Reserve, Sumatra) were used. The results of Fisher Ã¡diversity indexes across all sites of Gunung Patuha, showed that the second site(1,900 m asl.) was the highest (85.48). On the other hand, the third site (2,250 m asl.)was the lowest (45.70). The species composition of those sites were also different. Atthe first site, Pyralid and Noctuid moths were dominant, while at the second and thethird sites, Geometrid and Noctuid moths were dominant. Moreover, pyralid mothsincrease gradually along with the decrease of gradient altitude at this forest. Comparedwith other data, the diversity of macro-moths at Gunung Patuha was slightly lower thanthose of the two submontane forests, Gunung Botol and Gunung Kendeng but higherthan that of Giam Siak Kecil, they were 117.26, 179, 117.4 and 47.68, respectively.